Maintenance Culture And Performance Of Selected Manufacturing Firms In Benue State, Nigeria. - Chiekezie, Obianuju Mary; NZEWI, DR HOPE NGOZI; ODEKINA, FELICIA (Archives of Business Research, 2017)
Manufacturing firms in Nigeria continuously face the problem of stoppage of production processes and high cost of repair due to inadequate knowledge of maintenance culture. The study seeks to examine the extent to which maintenance culture influences performance of selected manufacturing firms in Benue State, Nigeria. The specific objective is to ascertain the extent to which preventive maintenance influences product delivery of selected firms. The study adopted survey design with a population of two hundred and thirty three (233) and a sample size of one hundred and forty seven (147) derived using Taro Yamane’s formula for finite population. Questionnaire was used as instrument for data collection. Data collected were analyzed with the use of Pearson Product Moment Correlation. The r value was subjected to a t-test of significance. Result shows that preventive maintenance significantly influences product delivery of the selected firms. The study recommended among others that firms should continuously adopt preventive and corrective measures of maintenance to reduce cost of repairs and intermittent stoppage of production processes. Firms should embark on continuous training programmes for their maintenance personnel as a pillar for proper maintenance culture development.